PENATALAKSANAAN FISIOTERAPI PADA KONDISI FROZEN SHOULDER DEXTRA DENGAN MENGGUNAKAN MODALITAS HOLD RELAX EXERCISE DAN MOBILIZATION WITH MOVEMENT (MWM) - Silfi Nur Haliza; Indah Permata Sari; Faridah Faridah (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2022)
Background: Frozen shoulder is a shoulder condition in which there is a gradual reduction in active and passive range of motion (ROM) and pain in all areas of movement of the glenohumeral joint, especially external rotation, caused by progressive fibrosis and contracture of the glenohumeral joint capsule. This situation is initially characterized by shoulder pain that arises slowly then the pain becomes sharper, limitations of motion appear, and stiffness of the shoulder joint. Objective: This study aims to determine the management of physiotherapy in frozen shoulders using hold relax exercise and mobilization with movement (MWM) modalities. Result: supporting journals about the use of Hold relax exercise and Mobilization with movement methods can reduce pain and increase Lgs in Frozen Shoulder patients with a dose of 3 times a week and the results show that there is a decrease in pain in Frozen Shoulder patients. Conclusion: Hold Relax Exercise and Mobilization with Movement can reduce pain, and increase functional activity in Frozen Shoulder sufferers. Key words : Hold Relax Exercise and Mobilization With Movement